2012
DOI: 10.1177/0892705712443249
|View full text |Cite
|
Sign up to set email alerts
|

Properties of clay nanocomposites based on poly(vinylidene fluoride-co- hexafluoropropylene)

Abstract: Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) nanocomposites with different contents of nanoclays were prepared by melt mixing. The clays used included unmodified clays, a commercially available hydrophilic nanoclay based on bentonite (nanoclay 1) and organically modified clay based on montmorillonite (nanoclay 2). The nanocomposites obtained were analyzed by x-ray diffraction, differential thermal and differential scanning calorimetry analyses and their basic tensile and other characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…The result confirms the increased amorphisity in the irradiated polymer film. 31,32 This observation is in correlation with the XRD results.…”
Section: Resultssupporting
confidence: 87%
“…The result confirms the increased amorphisity in the irradiated polymer film. 31,32 This observation is in correlation with the XRD results.…”
Section: Resultssupporting
confidence: 87%
“…The T C and T m of the composites on the other hand were generally equal to slightly higher than for the polymer, possibly indicating a somewhat more perfect crystalline phase. The decrease of crystallinity with addition of clay has been observed in other studies; however, the β phase fraction is usually reported to increase . In this case, it seems that the presence of clay somewhat hindered the growth of β phase crystals during annealing, so that the fraction of β phase increased more rapidly with annealing time in the polymer than in the composites, although eventually reached similar values in all materials.…”
Section: Resultssupporting
confidence: 72%
“…In addition, for the dielectric properties of PVDF, ceramics, and graphene oxide were usually used as fillers to further enhance the dielectric properties of pure PVDF. Moreover, the dielectric and piezoelectric properties could be enhanced simultaneously by adding nanoparticles (such as Fe 2 O 3 and Co 3 O 4 ), metallic nanoparticles (such as triturated copper and cobalt), and clay (montmorillonite [MMT]) as fillers in the PVDF‐ co ‐hexafluoropropylene (PVDF‐HFP) matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Clay minerals, such as MMT, kaolinite, halloysite, attapulgite, palygorskite, and sepiolite (SEP), were widely used as green fillers in polymer matrix in order to enhance the performance of polymer, such as the phase crystallization and electrical properties . For the MMT/PVDF composites reported previously, the piezoelectric and dielectric could be improved at the same time . The MMT induced the polarization of PVDF‐HFP by the hydrogen bonds between F atoms of PVDF‐HFP and OH of MMT.…”
Section: Introductionmentioning
confidence: 99%